The environment and nursing: their interfaces and inclusion in undergraduate programs - Bruzos, Gabriela Azevedo de Souza; Kamimura, Helayne Mika; Rocha, Suelen Alves; Jorgetto, Thais Amanda Calori; Patrício, Karina Pavão (Saúde e Sociedade, 2011)
Environmental degradation has been quickly changing our scenario and negatively interfering in the health-disease process of the whole community. However, the environment has been conceived as a simple scenario, something external to the human being, instead of where we are included and where interactions and inter-relations occur. The complexity of environmental problems claims for the adoption of measures that can overcome assistentialist practices, leading to the adoption of trans-disciplinary practices that can advance in healthcare promotion. In this article, an attempt is made to discuss, in this perspective, the need to include the topic 'health and the environment' in undergraduate healthcare programs by taking as an example a Nursing program in the state of São Paulo, Brazil, which has included it as one of its disciplines. It also analyzes the nurse's role in the relationship with the environment according to the students' social representation and based on the Collective Subject Discourse. It is fundamental to discuss the whole environmental topic among healthcare professionals, so that they can acquire such knowledge and develop skills to identify environment-related problems. In this way, they will be able to propose problem-solving and preventive actions together with the community, aiming at reducing the environmental risks to which everyone is exposed. The depth of healthcare professionals' roles in view of environmental problems is reinforced, as they seek for healthcare in an enlarged perspective of health promotion.